Suppression of transforming growth factor β signalling aborts caerulein induced pancreatitis and eliminates restricted stimulation at high caerulein concentrations. Issue 5 (29th November 2006) - Wildi, Stefan; Kleeff, Jörg; Mayerle, Julia; Zimmermann, Arthur; Böttinger, Erwin P; Wakefield, Lalage; Büchler, Markus W; Friess, Helmut; Korc, Murray
Abstract : Background: Transforming growth factors βs (TGF-βs) are implicated in pancreatic tissue repair but their role in acute pancreatitis is not known. To determine whether endogenous TGF-βs modulate the course of caerulein induced acute pancreatitis, caerulein was administered to wild-type (FVB−/−) and transgenic mice that are heterozygous (FVB+/−) for expression of a dominant negative type II TGF-β receptor. Methods: After 7 hourly supramaximal injections of caerulein, the pancreas was evaluated histologically and serum was assayed for amylase and lipase levels. Next, the effects of caerulein on amylase secretion were determined in mouse pancreatic acini, and cholecystokinin (CCK) receptor expression was assessed. Results: The normal mouse pancreas was devoid of inflammatory cells whereas the pancreas from transgenic mice contained lymphocytic infiltrates. Caerulein injection in wild-type mice resulted in 6- and 36-fold increases in serum amylase and lipase levels, respectively, increased serum trypsinogen activation peptide (TAP) levels, gross oedema and a marked inflammatory response in the pancreas that consisted mainly of neutrophils and macrophages. By contrast, FVB+/− mice exhibited minimal alterations in response to caerulein with attenuated neutrophil–macrophage infiltrates. Moreover, acini from FVB+/− mice did not exhibit restricted stimulation at high caerulein concentrations, even though CCK receptor mRNA levels were not decreased. Conclusion: Our findings indicate that a functional TGF-β signalling pathway may be required for caerulein to induce acute pancreatitis and for the CCK receptor to induce acinar cell damage at high ligand concentrations. Our results also support the concept that restricted stimulation at high caerulein concentrations contributes to the ability of caerulein to induce acute pancreatitis.